2018
DOI: 10.1002/mdc3.12688
|View full text |Cite
|
Sign up to set email alerts
|

Levodopa‐Induced Neuropathy: A Systematic Review

Abstract: Background Background: Clinical, neurophysiological, and pathological evidence suggest an association between Parkinson's disease (PD) and peripheral neuropathy (PNP), with a possible causative role of levodopa metabolic products, such as homocysteine and methylmalonic acid. Methods Methods: We conducted a systematic review of studies reporting cases of PNP in L-dopa-treated PD patients indexed in PubMed between January 1990 and March 2018. ResultsResults: We identified 38 articles reporting cases of PNP in PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
53
3
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 66 publications
(173 reference statements)
4
53
3
4
Order By: Relevance
“…39,40 A recent systematic review revealed that over one-third of PD patients in treatment with L-dopa may develop polyneuropathy, with a significantly higher prevalence of acute and subacute forms in those receiving LCIG. 41 It has been hypothesized that a high-dose of LD favors high levels of homocysteine and methylmalonic acid or reduces the absorption of vitamins (B6, B12) and folate. Vitamin B6 and folate deficiency in the setting of LCIG infusion have been associated with weight loss and subacute axonal sensorimotor polyneuropathy.…”
Section: Deterioration Of General Condition 8 24%mentioning
confidence: 99%
“…39,40 A recent systematic review revealed that over one-third of PD patients in treatment with L-dopa may develop polyneuropathy, with a significantly higher prevalence of acute and subacute forms in those receiving LCIG. 41 It has been hypothesized that a high-dose of LD favors high levels of homocysteine and methylmalonic acid or reduces the absorption of vitamins (B6, B12) and folate. Vitamin B6 and folate deficiency in the setting of LCIG infusion have been associated with weight loss and subacute axonal sensorimotor polyneuropathy.…”
Section: Deterioration Of General Condition 8 24%mentioning
confidence: 99%
“…Other studies have indicated a link between polyneuropathy and a higher levodopa equivalent daily dose [28]. However, other factors may be linked to levodopa-related polyneuropathy, including a disruption in the metabolic breakdown of levodopa, causing low levels of vitamin B12, vitamin B6, and folate [28,29] and high homocysteine and methylmalonic acid [28][29][30] and/or BMI reduction [30]. Levodopa-related polyneuropathy is evidently a complex phenomenon that requires careful monitoring of neuropathic symptoms and vitamin deficiencies, particularly when higher levodopa doses are used.…”
mentioning
confidence: 96%
“…Some studies have suggested that the frequency of polyneuropathy is more likely to be associated with the duration of the cumulative exposure than with peak doses during LCIG therapy [26,27]. Other studies have indicated a link between polyneuropathy and a higher levodopa equivalent daily dose [28]. However, other factors may be linked to levodopa-related polyneuropathy, including a disruption in the metabolic breakdown of levodopa, causing low levels of vitamin B12, vitamin B6, and folate [28,29] and high homocysteine and methylmalonic acid [28][29][30] and/or BMI reduction [30].…”
mentioning
confidence: 99%
“…Es hat sich gezeigt, dass Höhe und Dauer der L-DOPA-Dosierung mit Hinweisen auf einen Vitamin-B12-Mangel und auch mit der Wahrscheinlichkeit einer Neuropathie korrelieren [7]. Daher sollte vor allem bei Patienten mit Morbus Parkinson, Langzeit-L-DOPA-Therapie und PNP an einen Vitamin-B12-Mangel gedacht werden [33].…”
Section: Polyneuropathien Durch Vitaminmangelunclassified